A forensic framework and decision support system for harmonized and holistic food system resilience and sustainability analysis - Agyemang, Prince; Kwofie, Ebenezer M.; Dessureault, Marie-Anne; Ulimwengu, John M. (AKADEMIYA2063, 2023)
Today, many innovative food system transformation programs are taking place in several parts of the world, including developing, and low-income countries as well as those in Africa south of the Sahara (Benfica et al. 2023). Notably, in Africa, food systems are at a crossroads, facing several endogenous and exogenous shocks and stressors. Approximately 282 million people in Africa are undernourished, with a prevalence of 22.8 percent as measured by the prevalence of undernourishment, a Sustainable Development Goal (SDG) indicator (FAO et al. 2017; Agyemang and Kwofie 2021). Furthermore, continuous floods and droughts in many parts of the continent have reduced food security and calorie intake, respectively, by 5–20 percent and 1.4 percent below 2019 levels (Balgah et al. 2023). By 2050, climate change is anticipated to slow the fight against hunger, with an estimated 78 million people in Africa projected to experience chronic hunger in addition to the current numbers (Hasegawa et al. 2018). The individual and combined effects of external shocks and stressors on the African food system, including climate change, soil degradation, price fluctuations, political conflict, and widespread fragility, have created a complex risk environment that threatens food security and the overall well-being of many Africans. Against the above background, there is a consensus within the scientific and policy advocacy community that the African food system is flawed.